Multum in parvo. Eight examples from the Louros Archive - Diamandopoulos, Athanasios (DELTOS, 2024)
This paper begins with a brief overview of the late Professor Nikolaos Louros’ life, his residence, the eponymous Foundation for the History of Medicine, and his Archive. The main focus is the presentation of eight short entries from the Archive, which initially appear to concern medical matters. However, further research reveals their significance in shedding light on major political, social, and cultural events in Greece. The content of these eight notes includes: One and two - Louros’ instructions concerning the fate of his Archive after his death. Three - the peculiar circumstances surrounding the delivery of Queen Geraldine of Albania’s first son. Four - Louros’ appointment as director of the Evangelismos Hospital’s Department of Gynaecology. Five - a case of hymenorrhaphy. Six - events coinciding with the delivery of the Argentine Ambassador’s wife, Seven and eight - The tracing of Louros’ tomb.